2022
DOI: 10.2147/ijn.s373777
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Liposomes Combined with 5-Fluorouracil Inhibits Angiogenesis and Tumor Growth of APC (Min/+) Mice and AOM/DSS-Induced Colorectal Cancer Mice

Abstract: Background Transgenic C57BL/6-APC (Min/+) spontaneous cancer mouse model and the Azoxymethane (AOM)/Dextran Sulfate Sodium (DSS) chemically induced orthotopic colorectal cancer mouse model represented distinct pathogenesis of colorectal cancers. Our previous study revealed that the combination of Rapamycin liposomes (Rapa/Lps) and 5-Fluorouracil (5-FU) has anti-colorectal cancer effects. However, the therapeutic efficacy of Rapa/Lps and 5-FU in other colorectal cancer mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Subsequently, we replicated this cycle thrice to induce colorectal cancer (CRC) in mouse models [25] . Finally, the mice were euthanized by cervical dislocation using isoflurane (R510–22–10, RWD Life Science, Shenzhen, China).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, we replicated this cycle thrice to induce colorectal cancer (CRC) in mouse models [25] . Finally, the mice were euthanized by cervical dislocation using isoflurane (R510–22–10, RWD Life Science, Shenzhen, China).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, treatment of skin cancer with phototherapy effect of liposomal nanocarriers can be facilitated [57] . According to the studies, it is highly suggested to use liposomes for purpose of cancer therapy and chemotherapy due to their high potential [58] , [59] , [60] , [61] and in next section, use of liposomes for HCC treatment is discussed ( Fig. 1 ).…”
Section: Liposomes In Cancer Therapy: a Summarymentioning
confidence: 99%
“…The histological analysis of Apc mutation-induced tumors of the colon revealed that they are benign adenomas, making this model appropriate for investigating the premalignant rather than malignant phases of CRC. Nevertheless, tumor malignancy increases, and latency time shortens when AOM or other carcinogenic compound is administered [117,119,120]. Despite the fact that additional Apc-targeting murine models have been developed (Apc ∆716 , Apc ∆14 , Apc 1638N , among others), Apc Min/+ continues to be the most widely employed transgenic murine model of CRC [43].…”
Section: Adenomatous Polyposis Mouse Models (Apmm)mentioning
confidence: 99%